2008
DOI: 10.1362/026725708x345506
|View full text |Cite
|
Sign up to set email alerts
|

Marketing/accounting synergy: a discussion of its potential and evidence in e-business planning

Abstract: Abstract:Advances in technology create opportunities for new forms of arranging work, such as collapsing the boundaries between marketing and accounting. This makes it possible for management to identify the key attributes and processes required for a more integrated marketing/ accounting process. This paper sheds light on how e-business planning is taking place and identifies the key areas that are, together, acting as barriers to aligning organisation design, structures and people in the digitized world. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Nguyen and Doan, 2016;Phillips and Halliday, 2008;Sidhu and Roberts, 2008) with the combination between MO (a marketing variable) and the use of MAS (an accounting variable) in the theoretical model. The findings suggest that firms need to combine marketing strategy (via MO) and MAS to achieve superior firm performance.…”
mentioning
confidence: 99%
“…Nguyen and Doan, 2016;Phillips and Halliday, 2008;Sidhu and Roberts, 2008) with the combination between MO (a marketing variable) and the use of MAS (an accounting variable) in the theoretical model. The findings suggest that firms need to combine marketing strategy (via MO) and MAS to achieve superior firm performance.…”
mentioning
confidence: 99%
“…They have responded with expanded internal and external reporting and third party auditing, in the hope that these measures will produce positive consequences. While expanded auditing perpetuates a 'sciencey' regime of truth claiming, it does little to address the intensified general scepticism associated with a prevailing climate of institutional risk (Power et al, 2009) or the demands to build better understanding through dialogue in a Web 2.0 environment (Phillips & Halliday, 2008). In this paper we expand on what other authors have stated, 'that there should be more to accounting than "counting"' (Roslender & Wilson, 2008, p. 872).…”
Section: Disclosure and Accountabilitymentioning
confidence: 86%
“…The digitalization and social media technologies have enlivened the discussion around marketing performance measurement during the last ten years (Gleaves et al, 2008;Phillips and Halliday, 2008 We found that the marketing communications measurement must be company specific (Seth and Sisodia, 2002) and have its roots in the company's business strategy (Phillips and Halliday, 2008). Measurement practices should examine how both long-term objectives and short term objectives are met (Ambler and Roberts, 2008 qualitative, quantitative and financial (ROI) (see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Marketing performance measurement has to be seen in the context of the whole company (Phillips and Halliday, 2008). To know whether the marketing objectives or whole company's business objectives are met or not, the company needs regular marketing measurement.…”
Section: Marketing Communications Metricsmentioning
confidence: 99%
See 1 more Smart Citation